Assessment of Building Roof Defects Using Unmanned Aerial Vehicle (UAV) and Condition Survey Protocol (CSP) 1 Matrix System - Mohd Azri, Muhammad Rusyaidi; Syed Mohamad, Syed Burhanuddin Hilmi (Recent Trends in Civil Engineering and Built Environment, 2023)
In Malaysia, inspecting the roof structure of a high structural building usually takes a long time and costs a lot of money. Furthermore, defects in difficult areas of the building are difficult to detect. As a result, this study was carried out at the Faculty of Civil Engineering and Built Environment (FKAAB), UTHM to assess the extent to which Unmanned Aerial Vehicle (UAV) can be used to inspect building roof structures and analysed the significant building defects to the level of functionality using the Condition Survey Protocol (CSP) 1 Matrix. DJI Phantom 4 Pro was the type of UAV used to capture images of the defect and then processed by Pix4Dmapper software. The processed defect images were analysed using the CSP 1 Matrix to determine whether the building's overall performance. FKAAB's overall roof condition was average, with a total score of 5.95. As conclusion, a UAV can be used to inspect buildings because all the defects on the roof structure can be identified from the images captured by the UAV and can be analysed using CSP 1 Matrix as an assessment for evaluating the defect and overall roof condition.